Model Penyelesaian Kredit Macet Kud Perintis Utama Oleh Pemerintahan Dusun Tuo Limbur - Miranti, Miranti; Amiruddin, Amiruddin (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2022)
This study aims to analyze internal factors and external factors with the settlement model of bad loans in the cause of bad debts at KUD Perintis Utama, Limbur Lubuk Mengkuang District. The data of this research were obtained from interviews (Primary) directly from the Cooperative Unit of the Main Pioneer Village and several documents. Research findings show that the internal factors that cause bad debts at the Tuo Limbur Village Unit Perintis Utama Cooperative are negligence on the part of creditors in complying with the approval of the granting of credits that have been confirmed, it is too easy to give receivables due to the absence of clear benchmarks on wealth standards, cash flow developments. old debtor users. While the external factor is the decline in the company's economic condition caused by the decline in general economic conditions and the business fields in which they operate, the bad character of the debtor who originally planned to not pay off his receivables. The efforts of the Main Pioneer Village Unit Cooperative in dealing with bad loans include Age cannot be more than 60 years old, there is a recommendation from Rio (Village Head), adjusted to a minimum income of 2 hectares with a maximum income of 100 million and is not allowed to sell with palm oil tokens. condition of economy), payment is adjusted to the income result where 25% of farmers' income is for payment of bad credit, credit restructuring or improvement efforts carried out by KUD in credit activities for debtors who have difficulty fulfilling their obligations.